The Policy Interest-Rate Pass-Through in Central America - Medina Cas, Stephanie (IMF Working Papers; Working Paper, 2011)
Several Central American (CADR) central banks with independent monetary policies have adopted policy interest rates as their main instrument to signal their monetary policy stances, often in the context of adopting or transitioning to inflation targeting regimes. This paper finds that the interest-rate transmission mechanism, or the pass-through of the policy rate to market rates, is generally weaker and slower in CADR than in the LA6, the countries selected as benchmarks. A variety of potential factors behind this finding are examined, including the degrees of financial dollarization, exchange rate flexibility, bank concentration, financial sector development, and fiscal dominance. Through panel data analysis, the study suggests that the transmission mechanism can be strengthened by increasing exchange rate flexibility, and, over time, by adopting measures towards reducing financial dollarization, developing the financial sector, and reducing bank concentration.